Lucretian subversion: Animal speech and misplaced wonder in Paradise Lost 9.549-66 - Allendorf, K (Wiley, 2018)
The language used by the Satanic serpent in his encounter with Eve in Book 9 of Paradise Lost is key to Eve's subsequent temptation and eventual Fall. The first danger of the temptation scene, as John Leonard has argued, lies in her being drawn into a debate about the nature of the serpent's speech: “[T]he serpent speaks specifically about his speaking and attributes this supposedly new power to some as yet unspecified fruit” (141). He not only provides Eve with an account of how he came to possess the human gift of language, but also outlines how he came to possess the cognitive faculties that underlie it (PL 9.598–601). In what follows, I argue that the scene functions as a counter‐didactic experience for Eve, specifically in its allusive reworking of a passage on the origins of language in the Roman Epicurean poet Lucretius's didactic poem On the Nature of Things (De Rerum Natura, henceforth DRN). The key to the success of Eve's temptation in Book 9 is the way the exchange employs and subverts elements of this Lucretian account of language in DRN 5, announcing the confusion of Eve's cognitive faculties, and building the language of misplaced wonder that subverts the didactic message of Lucretius's poem.